High-temperature-resistant wave-transparent heat-insulating aerogel material and preparation method thereof

Through the combination of silicon sol, aluminum sol and wave-transmissive-light-shading dual-function additives, combined with impregnated gel and supercritical drying process, a high-temperature wave-transmissive thermal insulation aerogel material was prepared, solving the problem of existing materials at high temperatures The problem of insufficient thermal insulation performance has achieved low density, high efficiency thermal insulation and stability improvement.

CN119161167APending Publication Date: 2024-12-20AEROSPACE INST OF ADVANCED MATERIALS & PROCESSING TECH

Patent Information

Application Number
CN202411183033.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-27
Publication Date
2024-12-20

AI Technical Summary

Technical Problem

Existing wave-transmitting insulation materials are difficult to combine lightweight, efficient heat insulation and low dielectric loss at high temperatures, and the process is complex or requires expensive additives, which affects the performance and stability of the material.

Method used

Silicon sol and aluminum sol are configured as a mixed sol, and wave-translucent-blocking dual-function additive nanopowder and dispersant are added to prepare high-temperature wave-translucent thermal insulation aerogel materials through impregnation gel and supercritical drying processes, and at high temperatures Heat treatment is carried out to simplify the process flow, and achieve uniform dispersion and efficient heat insulation.

Benefits of technology

The prepared material has low density, dielectric constant and dielectric loss within a suitable range, and its thermal conductivity is lower than that of ordinary aerogel materials. It has high temperature insulation performance above 1200℃, which simplifies the process flow and improves the stability of the material. performance and performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119161167A_ABST
    Figure CN119161167A_ABST
Patent Text Reader

Abstract

The invention discloses a high-temperature-resistant wave-transparent heat-insulating aerogel material and a preparation method thereof, and belongs to the field of gel materials. The preparation method comprises the following steps: preparing a mixed sol from a silica sol and an aluminum sol, adding a wave-transparent and light-shading dual-functional additive nano powder into water, and adding a dispersing agent to obtain a dispersion liquid; uniformly mixing the mixed sol, the dispersion liquid and ammonia water, and putting the mixture into a fiber felt for dipping gel; replacing the wet gel with an ethanol solvent for several times, and then carrying out supercritical drying; the aerogel is subjected to heat treatment at high temperature, and the high-temperature-resistant wave-transparent heat-insulation aerogel material is obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of gel materials, and in particular relates to a high-temperature resistant, wave-transmitting, heat-insulating aerogel material and a preparation method thereof. Background Art

[0002] In the aerodynamic heating environment of long-duration flight, the surface temperature of the aircraft will quickly reach 1000-1500℃ or even higher. In order to ensure the normal operation of internal communication, telemetry, guidance and other systems, the thermal protection system is required to be highly efficient in heat insulation without affecting the signal transmission and reception of the aircraft. This puts forward the requirements for thermal insulation materials to be high temperature resistant, highly efficient in heat insulation and lightweight on the basis of low dielectric constant and low dielectric loss.

[0003] At present, the commonly used wave-transmitting heat-insulating materials mainly include ceramic heat-insulating tile materials, glass fiber felt materials and aerogel composite materials. The main problem of ceramic heat-insulating tiles is that their density is too high and their dielectric properties are poor. Glass fiber felt has a large defect in thermal conductivity, and it is difficult to achieve efficient heat insulation at high temperatures. As a new type of porous nanomaterial, aerogel composite materials have unique advantages in density and dielectric properties, but it is urgent to solve the problem of rapid increase in thermal conductivity caused by transparency to infrared radiation at high temperatures. For example, patent CN112552064A introduces a lightweight wave-transmitting heat-insulating tile material, which uses a semi-dry-wet two-step fiber dispersion method. Compared with traditional rigid heat-insulating tile materials, it has improved in density and dielectric constant, but its dielectric loss and thermal conductivity are still high. Patent CN106630931A introduces a fiber-reinforced alumina-silicon oxide aerogel material, which is a wave-transmitting heat-insulating integrated aerogel material prepared by a one-step sol-gel method, but its density and dielectric constant are too high. Patent CN108383486A introduces a chromium-containing fiber-reinforced silica aerogel material. Chromium oxide is introduced into the aerogel system through the complexation and hydrolysis of chromium salts to improve the thermal insulation performance of the material, but its density is high and the temperature resistance level is insufficient. Patent CN111043450A introduces a new type of wave-transmitting thermal insulation component that combines thermal insulation tiles and aerogel materials, combining the thermal insulation performance and dielectric properties of aerogel materials and the mechanical properties of thermal insulation tile materials, but its structure is complex and easy to delaminate and age during use. In addition, patent CN107032736A uses chromium nitrate as a raw material, which is converted into chromium oxide in subsequent steps. The disadvantages are: first, a post-processing step of converting the auxiliary agent precursor into an auxiliary agent is required, which makes the process complicated; secondly, the morphology and size of the auxiliary agent component generated by the conversion are uncontrollable, and the effect of directional regulation according to the specific use occasion cannot be achieved; finally, the soluble precursor is often relatively expensive, and in the preparation process, it will introduce excess impurity ions or species, affecting the material performance. Patent CN117645490A uses a kneading machine to directly knead the auxiliary agent. This method will inevitably lead to uneven dispersion of the auxiliary agent particles, causing particle agglomeration and sedimentation, etc., which affects the stability of material quality.

[0004] To sum up, although the current technical solutions can meet the needs of wave transmission and heat insulation to a certain extent, they still have defects in light weight, high temperature resistance, and high-efficiency heat insulation. Therefore, it is urgent to develop a composite material with multiple properties to meet the application needs in the aerospace field. Summary of the invention

[0005] The purpose of the present invention is to prepare a wave-transmitting material with high temperature resistance, high efficiency heat insulation and low density.

[0006] The present invention adopts the following technical solutions to achieve the above-mentioned purpose:

[0007] The present invention provides a method for preparing a high temperature resistant wave-transmitting heat insulating aerogel material, comprising the following steps:

[0008] 1) preparing a mixed sol with silica sol and aluminum sol; adding the wave-transmitting and light-shielding dual-functional auxiliary nano powder into water and a dispersant, and mixing them evenly to obtain a dispersion;

[0009] 2) uniformly mixing the mixed sol, dispersion and ammonia water obtained in step 1), and placing the fiber felt into the fiber felt for impregnation with the gel;

[0010] 3) replacing the wet gel obtained in step 2) with ethanol solvent several times and then performing supercritical drying;

[0011] 4) The aerogel obtained in step 3) is heat-treated at high temperature to obtain a high-temperature resistant, wave-transmitting, and heat-insulating aerogel material.

[0012] Furthermore, in step 1), the mass ratio of silica sol to aluminum sol is one of 1:3, 2:5, 1:2, 2:3, 1:1, 3:2, 2:1, 5:2, and 3:1.

[0013] Furthermore, in step 1), 1 part of the wave-transmitting and light-shielding dual-functional auxiliary agent nanopowder is added to 5 to 20 parts of water and 0.02 to 2 parts of a dispersant is added.

[0014] Furthermore, in step 1), the wave-transmitting and light-shielding dual-functional auxiliary agent is one of aluminum phosphate, chromium phosphate, chromium oxide, and chromium aluminum phosphate, and has a particle size of 50 to 500 nm.

[0015] Furthermore, in step 1), the dispersant is one of polyvinyl alcohol, polyacrylamide, polyvinyl pyrrolidone, sodium hexametaphosphate, and sodium pyrophosphate.

[0016] Furthermore, in step 2), the mass ratio of the mixed sol, the dispersion and the ammonia water is 1:(0.05-0.3):(0.02-0.2), and the concentration of the ammonia water is 0.5-4M.

[0017] Furthermore, in step 2), the fiber felt is one of mullite fiber felt and alumina fiber felt, and the fiber felt density is 0.05-0.2 g / cm 3 .

[0018] Furthermore, in step 2), the gel is immersed for 24 to 96 hours.

[0019] Furthermore, in step 3), the substitution is performed 2-4 times.

[0020] Furthermore, in step 4), heat treatment is performed at 600-1000° C. for 0.5-12 h.

[0021] The present invention also provides a high temperature resistant wave-transmitting heat insulating aerogel material, which is prepared by the above method.

[0022] The beneficial effects achieved by the present invention are as follows:

[0023] 1) The present invention dissolves the soluble precursor converted into the required auxiliary agent component through post-treatment in the glue solution to achieve homogeneous dispersion.

[0024] 2) The present invention introduces a dispersant for pre-dispersion, which allows the additive particles to be evenly dispersed in the precursor solution, without uneven distribution and sedimentation problems during the soaking of the fiber felt and post-processing stages; on the other hand, additive particles of a specific size can be directly incorporated into the system, avoiding various problems caused by species conversion. As a result, the wave-transmitting and heat-insulating dual-function additive particles can be fully dispersed in the system, while retaining the original morphology and size of the additive particles, thereby improving the wave-transmitting and heat-insulating properties of the aerogel composite material.

[0025] 3) The present invention does not involve a high-temperature hydrothermal reaction process, and the conditions are relatively simple; and the wave-transmitting and heat-insulating gel system can be constructed by mixing the gel in one step, which simplifies the operation process.

[0026] 4) The high temperature resistant wave-transmitting heat insulating aerogel material prepared by the present invention has a temperature resistance grade of above 1200°C, a dielectric constant of 1.17 to 1.25 from room temperature to 1200°C in the Ku band, and a dielectric loss of 9×10 -4 ~7×10 -3 Density 0.18g / cm 3 ~0.28g / cm 3 , which is lower than the widely used thermal insulation tile materials. The 10% deformation compressive strength is 1.2MPa~2.3MPa, and the thermal conductivity at 1200℃ is ≤0.1W / m·K. The high-temperature thermal insulation performance is significantly better than that of general aerogel materials, which can meet the needs of efficient thermal insulation. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 The present invention is a flow chart of preparing a high temperature resistant wave-transmitting heat insulating aerogel material.

[0028] Figure 2 This is a photo of a flat sample of the high-temperature resistant, wave-transmitting, and heat-insulating aerogel material prepared in Example 1.

[0029] Figure 3 This is a SEM image of the high temperature resistant, wave-transmitting and heat-insulating aerogel material prepared in Example 1. DETAILED DESCRIPTION

[0030] In order to make the various technical features and advantages or technical effects in the above technical solutions of the present invention more obvious and easy to understand, they are described in detail below with reference to the accompanying drawings.

[0031] Example 1

[0032] 1) Silica sol and aluminum sol are prepared into a mixed sol at a ratio of 1:3; 1 part of chromium oxide with a particle size of 500 nm is added to 5 parts of water and 0.02 parts of polyvinyl pyrrolidone are added, and stirred evenly. At this time, the chromium oxide in the dispersion is uniformly dispersed in the water without sedimentation.

[0033] 2) The mixed sol obtained in step 1) was mixed with the chromium oxide dispersion at a mass ratio of 1:0.05, and 0.05 mass ratio of 1M ammonia water was added. After stirring evenly, a 0.05 g / cm 3 The mullite fiber felt is immersed in it and gelled at room temperature for 24 hours.

[0034] 3) The wet gel block obtained in step 2) is replaced twice with ethanol solvent and then subjected to supercritical drying.

[0035] 4) The aerogel obtained in step 3) is heat treated at 600° C. for 12 h to obtain a high temperature resistant, wave-transmitting and heat-insulating aerogel material.

[0036] The density of the wave-transmitting heat-insulating aerogel material prepared under the conditions of this embodiment is 0.18 g / cm 3 , 10% deformation compressive strength 1.2MPa, 1200℃ thermal conductivity 0.086W / m·K, room temperature dielectric constant 1.17, dielectric loss 9×10 -4 , 1200℃ dielectric constant 1.22, dielectric loss 5×10 -3 .

[0037] The wave-transmitting heat-insulating aerogel material prepared in this embodiment is as follows: Figure 2 As shown, its SEM image is as follows Figure 3 As shown, the microstructure of the aerogel material can be seen from the SEM image, in which the skeleton structure of nanoparticle stacking and the wave-transmitting and heat-insulating dual-functional auxiliary agent particles can be observed.

[0038] Example 2

[0039] 1) Silica sol and aluminum sol are prepared into a mixed sol in a ratio of 2:3; 1 part of aluminum phosphate with a particle size of 200 nm is added to 10 parts of water and 0.1 part of polyacrylamide is added, and stirred evenly. At this time, the aluminum phosphate in the dispersion is uniformly dispersed in the water without sedimentation.

[0040] 2) The mixed sol obtained in step 1) was mixed with the aluminum phosphate dispersion at a mass ratio of 1:0.1, and 0.02 mass ratio of 4M ammonia water was added. After stirring evenly, a density of 0.1 g / cm 3 The alumina fiber felt was immersed in it and gelled at room temperature for 48 hours.

[0041] 3) The wet gel block obtained in step 2) was replaced with ethanol solvent 4 times and then subjected to supercritical drying.

[0042] 4) The aerogel obtained in step 3) is heat treated at 1000° C. for 0.5 h to obtain a high temperature resistant, wave-transmitting and heat-insulating aerogel material.

[0043] The density of the wave-transmitting heat-insulating aerogel material prepared under the conditions of this embodiment is 0.24 g / cm 3 , 10% deformation compressive strength 1.7MPa, 1200℃ thermal conductivity 0.094W / m·K, room temperature dielectric constant 1.18, dielectric loss 1×10 -3 , 1200℃ dielectric constant 1.24, dielectric loss 6×10 -3 .

[0044] Example 3

[0045] 1) Silica sol and aluminum sol are prepared into a mixed sol in a ratio of 2:1; 1 part of aluminum phosphate with a particle size of 50 nm is added to 20 parts of water and 2 parts of sodium pyrophosphate are added, and stirred evenly. At this time, the aluminum phosphate in the dispersion is uniformly dispersed in the water without sedimentation.

[0046] 2) The mixed sol obtained in step 1) was mixed with the aluminum phosphate dispersion at a mass ratio of 1:0.2, and 0.2 mass ratio of 2M ammonia water was added. After stirring evenly, a density of 0.1 g / cm 3 The mullite fiber felt is impregnated therein and gelled at room temperature for 48 hours.

[0047] 3) The wet gel block obtained in step 2) was replaced with ethanol solvent three times and then subjected to supercritical drying.

[0048] 4) The aerogel obtained in step 3) is heat treated at 800° C. for 3 h to obtain a high temperature resistant, wave-transmitting and heat-insulating aerogel material.

[0049] The density of the wave-transmitting heat-insulating aerogel material prepared under the conditions of this embodiment is 0.23 g / cm 3 , 10% deformation compressive strength 1.8MPa, 1200℃ thermal conductivity 0.092W / m·K, room temperature dielectric constant 1.18, dielectric loss 9×10 -4 , 1200℃ dielectric constant 1.24, dielectric loss 6×10 -3 .

[0050] Example 4

[0051] 1) Silica sol and aluminum sol are prepared into a mixed sol at a ratio of 3:1; 1 part of aluminum chromium phosphate with a particle size of 100 nm is added to 10 parts of water and 0.5 parts of polyvinyl alcohol are added, and stirred evenly. At this time, the aluminum chromium phosphate in the dispersion is uniformly dispersed in the water without sedimentation.

[0052] 2) The mixed sol obtained in step 1) was mixed with the aluminum chromium phosphate dispersion at a mass ratio of 1:0.3, and 0.5M ammonia water was added at a mass ratio of 0.1. After stirring evenly, a 0.2 g / cm 3 The alumina fiber felt was immersed in it and gelled at room temperature for 96 hours.

[0053] 3) The wet gel block obtained in step 2) was replaced with ethanol solvent 4 times and then subjected to supercritical drying.

[0054] 4) The aerogel obtained in step 3) is heat treated at 800° C. for 6 h to obtain a high temperature resistant, wave-transmitting and heat-insulating aerogel material.

[0055] The density of the wave-transmitting heat-insulating aerogel material prepared under the conditions of this embodiment is 0.28 g / cm 3 , 10% deformation compressive strength 2.3MPa, 1200℃ thermal conductivity 0.102W / m·K, room temperature dielectric constant 1.20, dielectric loss 1×10 -3 , 1200℃ dielectric constant 1.25, dielectric loss 7×10 -3 .

[0056] Comparative Example 1

[0057] Comparative Example 1 was prepared according to Example 1 disclosed in CN108383486 A.

[0058] Chromium nitrate was dissolved in ethanol solvent at a ratio of 1:2, and then stirred for about 20 minutes to make it completely dissolved. Then, a 1M ammonia solution was slowly added to the chromium nitrate solution, and slowly added dropwise until the pH value of the solution was 8. Stirring was continued for 30 minutes to obtain a chromium salt complex solution. Then, a vacuum was used to inject a 0.1 g / cm 3 In the quartz fiber reinforced matrix, after the sol-gel is formed, it is placed in a 100°C oven for drying, and then placed in a 600°C muffle furnace for treatment for 2 hours. The fiber preform is then placed in a mold, and the silica sol and the preform are composited by vacuum pressing molding. After that, it is aged at room temperature for 36 hours and at 90°C for 36 hours. After aging, the acetone solvent is replaced twice, and then supercritical carbon dioxide drying is performed. Then, methyltrimethoxysilane is used for gas phase hydrophobic and moisture-proof treatment to obtain a thermal insulation sample.

[0059] Comparative Example 2

[0060] Comparative Example 2 was prepared according to Example 1 disclosed in CN111410549A.

[0061] (1) preparing a fiber slurry according to a mass ratio of silicon nitride chopped fibers, starch, boron nitride and water of 1:0.2:0.03:40;

[0062] (2) pouring the fiber slurry into a mold and dehydrating it by suction filtration to obtain a wet blank, which is then pressed on a pressure molding machine to a thickness of 30 mm;

[0063] (3) drying the wet blank in an oven at 100° C. for 12 h to obtain a dry blank;

[0064] (4) The dry blank is placed in a high-temperature furnace and sintered at 1200°C for 1 hour to obtain a high-temperature resistant, low thermal conductivity, heat-insulating and wave-transmitting material.

[0065] The performance data of the high temperature resistant, wave-transmitting and heat insulating aerogel materials prepared in the above examples and comparative examples are shown in the following Table 1.

[0066] Table 1 Comparison of performance of high temperature resistant wave-transmitting heat insulation aerogel materials prepared in the examples and comparative examples

[0067]

[0068]

[0069] It can be seen from the test results in Table 1 that the high-temperature resistant wave-transmitting heat-insulating aerogel prepared by the present invention has a temperature resistance grade of above 1200°C and has good high-temperature heat-insulating performance; when a fiber felt with a lower density is used, it has excellent lightness and wave-transmitting performance, and when a fiber felt with a higher density is used, its compression strength can be greatly improved while maintaining good wave-transmitting heat-insulating performance.

[0070] Although the present invention has been disclosed as above by way of embodiments, it is not intended to limit the present invention. Appropriate modifications or equivalent substitutions of the technical solutions of the present invention made by ordinary technicians in the field should all be included in the protection scope of the present invention. The protection scope of the present invention shall be based on what is defined in the claims.

Claims

1. A method for preparing a high temperature resistant wave-transmitting heat insulating aerogel material, characterized in that: The following steps are involved: 1) preparing a mixed sol with silica sol and aluminum sol; adding the wave-transmitting and light-shielding dual-functional auxiliary nano powder into water and a dispersant, and mixing them evenly to obtain a dispersion; 2) uniformly mixing the mixed sol, dispersion and ammonia water obtained in step 1), and placing the fiber felt into the fiber felt for impregnation with the gel; 3) replacing the wet gel obtained in step 2) with ethanol solvent several times and then performing supercritical drying; 4) The aerogel obtained in step 3) is heat-treated at high temperature to obtain a high-temperature resistant, wave-transmitting, and heat-insulating aerogel material.

2. The preparation method according to claim 1, characterized in that In step 1), the mass ratio of silica sol to aluminum sol is one of 1:3, 2:5, 1:2, 2:3, 1:1, 3:2, 2:1, 5:2, and 3:

1.

3. The preparation method according to claim 1, characterized in that: In step 1), 1 part of the wave-transmitting and light-shielding dual-functional auxiliary agent nanopowder is added to 5 to 20 parts of water and 0.02 to 2 parts of a dispersant is added.

4. The preparation method according to claim 1, characterized in that: In step 1), the wave-transmitting and light-shielding dual-functional auxiliary agent is one of aluminum phosphate, chromium phosphate, chromium oxide, and chromium aluminum phosphate, and the particle size is 50 to 500 nm; the dispersant is one of polyvinyl alcohol, polyacrylamide, polyvinyl pyrrolidone, sodium hexametaphosphate, and sodium pyrophosphate.

5. The preparation method according to claim 1, characterized in that: In step 2), the mass ratio of the mixed sol, the dispersion and the ammonia water is 1:(0.05-0.3):(0.02-0.2), and the concentration of the ammonia water is 0.5-4M.

6. The preparation method according to claim 1, characterized in that: In step 2), the fiber felt is one of mullite fiber felt and alumina fiber felt, and the fiber felt density is 0.05-0.2 g / cm 3 .

7. The preparation method according to claim 1, characterized in that: In step 2), the gel is immersed for 24 to 96 hours.

8. The preparation method according to claim 1, characterized in that: In step 3), the substitution is performed 2-4 times.

9. The preparation method according to claim 1, characterized in that: In step 4), heat treatment is performed at 600-1000° C. for 0.5-12 h.

10. A high temperature resistant wave-transmitting heat insulating aerogel material, characterized in that: The invention is prepared by the preparation method according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Preparation method of fiber-reinforced Al2O3-SiO2 aerogel material with wave transmission and heat insulation integrated function

    CN106630931A

  • Wave-transmission and thermal-insulation material with high-temperature radiation resistance and preparation method of material

    CN107032736A

  • High temperature radiation resisting wave-transmission and heat-insulation material and preparation method thereof

    CN108383486A

  • Wave-transparent type heat-insulating and gas-blocking component and manufacturing method thereof

    CN111043450A

  • High-temperature-resistant low-thermal-conductivity heat-insulating wave-transmitting material and preparation method thereof

    CN111410549A

Cited By

  • High-temperature-resistant and wave-transparent silicon oxide aerogel composite material and preparation method thereof

    CN120328998A